Women in the Middle East : Past and Present - Keddie, Nikki R. (Book collections on Project MUSE., 2007)
Written by a pioneer in the field of Middle Eastern women's history, Women in the Middle East is a concise, comprehensive, and authoritative history of the lives of the region's women since the rise of Islam. Nikki Keddie shows why hostile or apologetic responses are completely inadequate to the diversity and richness of the lives of Middle Eastern women, and she provides a unique overview of their past and rapidly changing present. The book also includes a brief autobiography that recounts Keddie's political activism as one of the first women in Middle East Studies. Positioning women within their individual economic situations, identities, families, and geographies, Women in the Middle East examines the experiences of women in the Ottoman Empire and Turkey, in Iran, and in all the Arab countries. Keddie discusses the interaction of a changing Islam with political, cultural, and socioeconomic developments. In doing so, she shows that, like other major religions, Islam incorporated ideas and practices of male superiority but also provoked challenges to them. Keddie breaks with notions of Middle Eastern women as faceless victims, and assesses their involvement in the rise of modern nationalist, socialist, and Islamist movements. While acknowledging that conservative trends are strong, she notes that there have been significant improvements in Middle Eastern women's suffrage, education, marital choice, and health.